Structures of vertebrate Patched and Smoothened reveal intimate links between cholesterol and Hedgehog signalling - Kowatsch, C; Woolley, R; Kinnebrew, M; Rohatgi, R; Siebold, C (Elsevier, 2019)
The Hedgehog (HH) signalling pathway is a cell–cell communication system that controls the patterning of multiple tissues during embryogenesis in metazoans. In adults, HH signals regulate tissue stem cells and regenerative responses. Abnormal signalling can cause birth defects and cancer. The HH signal is received on target cells by Patched (PTCH1), the receptor for HH ligands, and then transmitted across the plasma membrane by Smoothened (SMO). Recent structural and biochemical studies have pointed to a sterol lipid, likely cholesterol itself, as the elusive second messenger that communicates the HH signal between PTCH1 and SMO, thus linking ligand reception to transmembrane signalling.